Making It Personal: Regime Type and Nuclear Proliferation. Issue 3 (20th November 2013) - Way, Christopher; Weeks, Jessica L. P.
<x xml:space="preserve">Abstract</x> Study after study has found that regime type has little or no effect on states' decisions to pursue nuclear weapons. We argue, however, that conventional approaches comparing the behavior of democracies to that of nondemocracies have resulted in incorrect inferences. We disaggregate types of nondemocracies and argue that leaders of highly centralized, "personalistic" dictatorships are particularly likely to view nuclear weapons as an attractive solution to their concerns about regime security and face fewer constraints in pursuing nuclear weapons than leaders of other types of regimes. Combining our more nuanced classification of regime type with a more theoretically appropriate empirical approach, we find that personalist regimes are substantially more likely to pursue nuclear weapons than other regime types. This finding is robust to different codings of proliferation dates and a range of modeling approaches and specifications and has significant implications for both theory and policy.